Kulturně antropologické aspekty muzejního fenoménu - Petra Šobáňová (AntropoWebzin)
The study discusses the specific cultural human act, which is the tendency to gather and, in the spite of the time action, save important and representative, but also seemingly silly tangible things, documenting the human acts and the development of their world. By the realization of this tendency, which the museology calls the musealization and which it observes as its contentual domain, here it is not only cultural but also culture-creational human behaviour.The study contains the explication of the basic muzeologist term and ways out so especially the characteristics of the muzealization process and it´s result in the form of museum as well. It focuses not just on the institution of the modern museum, but also on the larger museum phenomena and its culturally anthropological aspects, which they manifests in its historical but also entirely nowadays forms. Study in short also explains the historical development of the museum´s phenomena and the modern museum as its institutional form. It also touches the problems and the visions of the nowadays museum in the world of the new technologies and the digitalization, which transforms accustomed ways of the presentation of collections and the view on the traditional museum function.